Investigating Students' Motivation to Speak English in EFL Classroom - Ferdy Satrio Andhara; Alfian Alfian (PT ARRUS Intelektual Indonesia, 2023)
Owning a motivation to learn the English language can act as a catalyst to success in the student’s professional career. Nonetheless, the student’s English proficiency and motivation to learn English cannot be attained unless the teacher implemented some strategies in the classroom. This prompted the researcher to investigate students’ motivation despite their shortcomings in the EFL classroom. The study aims to investigate students’ motivation and explore the teacher’s strategies to motivate students. The study was conducted by a case-study design using secondary students as participants. The findings indicated that the students were equally motivated to learn English, either intrinsic or extrinsic.